High performance optical oxygen sensors based on iridium complexes exhibiting interchromophore energy shuttling. Issue 10 (20th April 2016) - Medina-Rodríguez, Santiago; Denisov, Sergey A.; Cudré, Yanouk; Male, Louise; Marín-Suárez, Marta; Fernández-Gutiérrez, Alberto; Fernández-Sánchez, Jorge F.; Tron, Arnaud; Jonusauskas, Gediminas; McClenaghan, Nathan D.; Baranoff, Etienne
Abstract : Reversible electronic energy transfer is used for sensing oxygen traces and results in very high sensitivity. Abstract : A doubly pyrene-grafted bis-cyclometallated iridium complex with engineered electronically excited states demonstrates reversible electronic energy transfer between adjacent chromophores giving rise to extremely long-lived red luminescence in solution ( τ = 480 μs). Time-resolved spectroscopic studies afforded determination of pertinent photophysical parameters including rates of energy transfer and energy distribution between constituent chromophores in the equilibrated excited molecule ( ca . 98% on the organic chromophores). Incorporation into a nanostructured metal–oxide matrix (AP200/19) gave highly sensitive O2 sensing films, as the detection sensitivity was 200–300% higher than with the commonly used PtTFPP and approaches the sensitivity of the best O2 -sensing dyes reported to date.